Clonal Propogation of Kintamani Siam Orange (Citrus nobilis Lour) from Gamma Ray Irradiation - Lestari, Puji Wahyu; Defiani, Made Ria; Kosmiatin, Mia (Metamorfosa: Journal of Biological Sciences, 2022)
Kintamani siam citrus is favored as it has sweet taste, fragrant, and soft flesh. However, Kintamani siam citrus has a lot of seeds and less attractive skin color, so that it’s not popular as much as another citrus. An alternative to improve the quality of Kintamani siam citrus is through in vitro mutation induction using gamma rays. Putative mutant shoot of Kintamani siam citrus are propagated in vitro so that the duplicate of each mutant is obtained. The use of media types and growth regulators at the right concentration is one of the keys to success in tissue culture. This study aimed to determine the type of media that encourage the multiplication of shoots from nodus and internodus explants. Kintamani siam citrus plantlet produced from gamma ray irradiation was used as material with the following dosage 0, 4,5, 5, and 5,5 Gy. This study was in vitro multiplication of  shoots used explant nodus with the treatment of 7 types of media. The result of this study showed that nodus explant has successfully induced buds. Treatment of MS VMW + BAP 2 + GA 2 media was able to increase the number of buds as well, whereas MS VMW media was able to increase the number of leaves and as well as the number of roots. Key word: putative mutant , characterization, multiplication, mutation